Epidemiology and reporting characteristics of systematic reviews. - Moher, D; Tetzlaff, J; Tricco, A; Sampson, M; Altman, D (Public Library of Science, 2007)
BACKGROUND: Systematic reviews (SRs) have become increasingly popular to a wide range of stakeholders. We set out to capture a representative cross-sectional sample of published SRs and examine them in terms of a broad range of epidemiological, descriptive, and reporting characteristics, including emerging aspects not previously examined. METHODS AND FINDINGS: We searched Medline for SRs indexed during November 2004 and written in English. Citations were screened and those meeting our inclusion criteria were retained. Data were collected using a 51-item data collection form designed to assess the epidemiological and reporting details and the bias-related aspects of the reviews. The data were analyzed descriptively. In total 300 SRs were identified, suggesting a current annual publication rate of about 2,500, involving more than 33,700 separate studies including one-third of a million participants. The majority (272 [90.7%]) of SRs were reported in specialty journals. Most reviews (213 [71.0%]) were categorized as therapeutic, and included a median of 16 studies involving 1,112 participants. Funding sources were not reported in more than one-third (122 [40.7%]) of the reviews. Reviews typically searched a median of three electronic databases and two other sources, although only about two-thirds (208 [69.3%]) of them reported the years searched. Most (197/295 [66.8%]) reviews reported information about quality assessment, while few (68/294 [23.1%]) reported assessing for publication bias. A little over half (161/300 [53.7%]) of the SRs reported combining their results statistically, of which most (147/161 [91.3%]) assessed for consistency across studies. Few (53 [17.7%]) SRs reported being updates of previously completed reviews. No review had a registration number. Only half (150 [50.0%]) of the reviews used the term "systematic review" or "meta-analysis" in the title or abstract. There were large differences between Cochrane reviews and non-Cochrane reviews in the quality of reporting several characteristics. CONCLUSIONS: SRs are now produced in large numbers, and our data suggest that the quality of their reporting is inconsistent. This situation might be improved if more widely agreed upon evidence-based reporting guidelines were endorsed and adhered to by authors and journals. These results substantiate the view that readers should not accept SRs uncritically.